Pengembangan Soal Matematika Tipe Pisa Konten Bilangan untuk Literasi Matematis Siswa SMP - Syabaniah, Try Nurisa; Ratu Ilma Indra Putri; Zulkardi (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to develop a PISA-type test set based on real-world contexts integrated with strategies to see its effectiveness on junior high school students' mathematical literacy skills. The background of this study is the low achievement of Indonesian students' mathematical literacy in PISA, especially in Quantity content. The method used is design research with the Tessmer model through preliminary and formative evaluation stages (self-evaluation, expert review, one-to-one, and small group). The research subjects were students of class VIII.5 of SMP Negeri 11 Palembang. The results showed that the developed test set was very valid (82.9%) and practical (80%), and had very high reliability (α = 0.959). Students' mathematical literacy skills were in the high (33%), medium (50%), and low (17%) categories. The achievement of the Formulate indicator was 80.83%, Employ 76.94%, and Interpret 70.56%. These findings indicate that the problem set can strengthen students' mathematical literacy skills, especially in understanding context and developing problem-solving strategies, although mathematical interpretation and justification skills still need to be improved.   Keyword : Quantity content, Mathematical literacy skills, PISA type questions